Rihlatun ila alami addaynusurati - Stamper, Judith Bauer; Enik, Ted; Cole, Joanna (New York : Scholastic, 2006)
Ms. Frizzle's class travels on the Magic School Bus to the Mesozoic Era in order to study dinosaurs.
Text in Arabic.
Based on the Magic School Bus books written by Joanna Cole.
3-6
Keywords: Dinosaurs -- Fiction; Time travel -- Fiction; Arabic language materials; Dinosaurs -- Fiction; Time travel -- Fiction; Arabic language